O zabijaniu — uśmiercanie zwierząt przeznaczonych do celów gospodarczych w świetle przepisów rozporządzenia Rady WE nr 1099/2009 oraz regulacji krajowych - Gruszczyńska, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Legal articles aiming to protect animals from pain and suffering during killing process constitute one of the key areas of humanitarian animal protection regulations. Within the EU law, the Council Regulation EC No 1099/2009 of 24 September 2009 on the protection of animals at the time of killing constitutes the main act regulating this area Official Journal L 303 of 18.11.2009, pp. 1–30. The member countries have pledged to apply the said Regulation as of January 1, 2013. In order to assure its proper implementation it is necessary to introduce the EU regulations into domestic legislature, while simultaneously revoking the overlapping or conflicting domestic regulations. To date 15.12.2018, Poland has failed to fulfil the above obligation, while the application and interpretation of the EU and domestic regulations remain contentious. This results in the need to verify each particular case with regard to the applicable regulations by an entity responsible for commercial animal slaughter or by asupervisory body, which negatively impacts on the animal protection.In March 2016 the Minister of Agriculture and Rural Development presented adraft of an amendment to the Animal Protection Act for public consultation and settlement, whose aim is to implement the above-mentioned regulations. However, the proposed solutions evoke many questions and substantial doubts, while at the same time in the project implementation activities are lacking.The implementation of regulations ensuring proper application of the 1099/2009 Regulation should be considered crucial to guarantee the correct standards of protection of animals at the time of killing.
Keywords: EU law; Regulation EC No 1099/2009; Poland; amendment to the Animal Protection Act